2005
DOI: 10.1038/ncb1343
|View full text |Cite
|
Sign up to set email alerts
|

Histone acetylation by Trrap–Tip60 modulates loading of repair proteins and repair of DNA double-strand breaks

Abstract: DNA is packaged into chromatin, a highly compacted DNA-protein complex; therefore, all cellular processes that use the DNA as a template, including DNA repair, require a high degree of coordination between the DNA-repair machinery and chromatin modification/remodelling, which regulates the accessibility of DNA in chromatin. Recent studies have implicated histone acetyltransferase (HAT) complexes and chromatin acetylation in DNA repair; however, the precise underlying mechanism remains poorly understood. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

23
561
4
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 552 publications
(592 citation statements)
references
References 35 publications
23
561
4
4
Order By: Relevance
“…Our present studies validated that Lys 430 and Lys 451 are indeed the substrates for SUMO1 and essential for DNA damage response. It has been shown that TIP60 regulates the ATM/ATR activation caused by ionizing radiation (Sun et al, 2005) and participates in UV-induced DNA damage repair (Murr et al, 2006). Identification of TIP60 sumoylation provides great insight into the molecular mechanisms underlying DNA damage responses to UV irradiation vs ionizing radiation.…”
Section: Discussionmentioning
confidence: 99%
“…Our present studies validated that Lys 430 and Lys 451 are indeed the substrates for SUMO1 and essential for DNA damage response. It has been shown that TIP60 regulates the ATM/ATR activation caused by ionizing radiation (Sun et al, 2005) and participates in UV-induced DNA damage repair (Murr et al, 2006). Identification of TIP60 sumoylation provides great insight into the molecular mechanisms underlying DNA damage responses to UV irradiation vs ionizing radiation.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the N-terminal lysine residues of histones H3 and H4 are acetylated during DSBs (Bird et al, 2002;Tamburini and Tyler, 2005). Consistent with this, NuA4-Tip60 HAT acetylates histone H4 at DSB sites and facilitates DSB repair (Bird et al, 2002;Murr et al, 2006). In addition to HATs, the SWI2/SNF2 superfamily (INO80, SWR1, SWI/SNF and RSC) chromatin remodeling complexes are recruited to DSB sites and facilitate alterations in the nucleosomal position.…”
Section: Introductionmentioning
confidence: 68%
“…Acetylation of the N-terminal lysines 5, 8, 12 and 16 within histone H4 (H4 K5/K8/K12/K16) is critical for NHEJ (Bird et al, 2002). TIP60 functions as an acetyltransferase for the N-terminal residues of histone H4 at DSB sites in both yeast and mammalian cells (Downs et al, 2004; Role of CBP/p300 in non-homologous end joining H Ogiwara et al Murr et al, 2006). However, it was not known whether TIP60 is required for NHEJ in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The p400/Tip60 ratio and cell proliferation L Mattera et al (Murr et al, 2006), this finding could merely be an indirect consequence of the activation of DDR pathways by p400 knockdown. Strikingly, Tip60 directly acetylates the DNA damage signaling protein ATM (Sun et al, 2005), therefore allowing its activation.…”
Section: Discussionmentioning
confidence: 96%